Strategi Pemasaran Online Produk Buah Beku di Tokopedia (Studi Kasus Freshjus Jakarta) - RIAMBARA ABDILLAH HAZAZI; MADE ANTARA; RATNA KOMALA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Online Marketing Strategies of Frozen Fruit in Tokopedia (A Case Study of Freshjus Jakarta) The marketing of frozen fruit in traditional and modern markets is still very rare in Indonesia. This study aims to identify internal and external factors, namely the strengths, weaknesses, threats, and opportunities for the development of the marketing business of frozen fruit of Freshjus in Tokopedia. In addition, it aims to formulate general and alternative strategies, and appropriate development programs to be applied to the marketing business of frozen fruit products of Freshjus at Tokopedia. This research is a descriptive, qualitative and quantitative research. General strategies for online marketing of Freshjus frozen fruit products in Tokopedia which are produced based on the IE matrix are in the first position, namely intensive strategies (market penetration, market development and product development). Meanwhile, SWOT analysis found 12 alternative strategies including (1) Structuring an electronic storage system that is updated all the time, (2) Adjusting margins and making prices more competitive, (3) Promotions in Tokopedia, (4) Increasing sales, (5) Offering bonuses to customers, (6) Utilizing increasingly sophisticated technology, (7) Participating in certain events, (8) Making direct sales with customers, (9) Advertising in other media.